2018
DOI: 10.3899/jrheum.171195
|View full text |Cite
|
Sign up to set email alerts
|

High Disease Activity Is Associated with Self-reported Depression and Predicts Persistent Depression in Early Rheumatoid Arthritis: Results from the Ontario Best Practices Research Initiative

Abstract: Depression in ERA is common and initial high disease activity is associated with the probability of depression and its persistence. This risk seems particularly modified in women with active disease and represents an area for targeted focus and screening. Future studies in ERA are needed to determine if intervening during the "window of opportunity" to control disease activity has the potential to mitigate the development and maintenance of adverse mental health outcomes, including depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Moreover, Kuriya et al . [32] demonstrated a significant association between high continuous disease activity, measured by the Clinical Disease Activity Index, and persistent depression.…”
Section: Depression and The Impact On Rheumatoid Arthritis Disease Comentioning
confidence: 99%
“…Moreover, Kuriya et al . [32] demonstrated a significant association between high continuous disease activity, measured by the Clinical Disease Activity Index, and persistent depression.…”
Section: Depression and The Impact On Rheumatoid Arthritis Disease Comentioning
confidence: 99%
“…These findings extend previous papers showing that CDAI scores were significantly associated with depression ratings. [64][65][66] In another study in RA, patients with depression showed higher ratings on TJCs, EGA, PGA, DAS-28, SDAI, and CDAI. 65 A cross-sectional study performed in The Kenyatta National Hospital showed that depression was accompanied by increased CDAI scores and lowered quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…From a neurobiological perspective, reduced expression of BDNF, but not serum levels of pro-inflammatory cytokines (59) or TNF-α (57), has been found in depressed patients with RA with respect to subjects without depression. In contrast, other studies have documented a relationship between MDD and the inflammatory state, defined by plasma CRP levels (73) or indirectly via clinical indices of RA activity (74). The implication of over-inflammation in the onset of mood symptoms in RA is also supported by the evidence of alterations in the micro-structure of brain white matter in subjects with RA and comorbid depression as a result of vasculitis, ischemic brain lesions, and dots of demyelination (75).…”
Section: Autonomic Nervous System and Affective Disorders In Rheumatomentioning
confidence: 99%